Targeting TBK1 Attenuates LPS-Induced NLRP3 Inflammasome Activation by Regulating of mTORC1 Pathways in Trophoblasts - Lee, Sohee; Shin, Jiha; Kim, Jong-Seok; Shin, Jongdae; Lee, Sung Ki; Park, Hwan-Woo (Frontiers in Immunology, 2021)
Pathological maternal inflammation and abnormal placentation contribute to several pregnancy-related disorders, including preterm birth, intrauterine growth restriction, and preeclampsia. TANK-binding kinase 1 (TBK1), a serine/threonine kinase, has been implicated in the regulation of various physiological processes, including innate immune response, autophagy, and cell growth. However, the relevance of TBK1 in the placental pro-inflammatory environment has not been investigated. In this study, we assessed the effect of TBK1 inhibition on lipopolysaccharide (LPS)-induced NLRP3 inflammasome activation and its underlying mechanisms in human trophoblast cell lines and mouse placenta. TBK1 phosphorylation was upregulated in the trophoblasts and placenta in response to LPS. Pharmacological and genetic inhibition of TBK1 in trophoblasts ameliorated LPS-induced NLRP3 inflammasome activation, placental inflammation, and subsequent interleukin (IL)-1 production. Moreover, maternal administration of amlexanox, a TBK1 inhibitor, reversed LPS-induced adverse pregnancy outcomes. Notably, TBK1 inhibition prevented LPS-induced NLRP3 inflammasome activation by targeting the mammalian target of rapamycin complex 1 (mTORC1). Thus, this study provides evidence for the biological significance of TBK1 in placental inflammation, suggesting that amlexanox may be a potential therapeutic candidate for treating inflammation-associated pregnancy-related complications.